Pelatihan Pembuatan Lulur Tradisional Berbahan Dasar TOGA di Kelompok Wanita Tani (KWT) Bagas Waras Boyolali: Training on Making Traditional Scrubs Based on TOGA at KWT Bagas Waras Boyolali - Darojati, Ulfa Afrinurfadhilah; Rohmani, Sholichah; Sasongko, Heru; Susanto, Nindita Clourisa Amaris; Zulpadly, M. Fiqri; Utami, Diyah Tri; Meitasari, Annisa Diyan; Untari, Meta Kartika; Ermawati, Dian Eka; Artanti, Anif Nur (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Bagas Waras Women's Farmers Group (KWT) is one of the women's groups that cultivates a lot of TOGA in Banyuanyar Village, Boyolali. Their seriousness in cultivating TOGA is proven by the establishment of Omah TOGA, which has become an educational tourism destination. KWT members also have high enthusiasm for developing TOGA's potential and have produced many processed food products from TOGA. KWT Bagas Waras needs innovations in TOGA products, namely traditional cosmetic products. The service team provides scientific insight through training on developing traditional cosmetic products, namely body scrubs made from various types of TOGA. This activity involves 40 KWT members who will participate in a series of stages: preparation, training, practice, and evaluation. This training activity can increase the scientific insight of KWT members and help them develop traditional body scrubs made from TOGA and good packaging methods. This training has gone well, with all participants very enthusiastically listening to material related to traditional cosmetics and demonstrating how to make body scrubs. The results obtained are traditional body scrubs with various variants originating from TOGA.